Evaluation of the most important elements for creating a positive work environment in MNCs - Mostova, Maria; Martínez Pantoja, Yadira Ixchel; Kloudová Jiřičková, Václava; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This study examines the impact of managerial factors on a positive work environment and identifies what the most important elements are for creating a positive work environment. The aim of this research is to investigate how leadership and management practices impact the creation of a positive work environment and what the key elements contribute to it. In order to find out which factors are more important for people in the work environment, a survey was conducted. These findings highlight the importance of certain elements for employees, such as work-life balance, rewards, and individual communication with managers. Furthermore, it offers recommendations on which strategies and elements can be used by managers in order to achieve a positive work environment in the organization, including managerial coaching as one of the recommended strategies.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses